Vegetation Composition and Structure of Sapling Community in Girimanik Natural Forest Area, Setren Village, Slogohimo District, Wonogiri - Almira Rahmadani Putri; Santhyami Santhyami; Lina Agustina (Universitas Labuhanbatu, 2025)
Stake plants, commonly known as saplings, are needed to enhance soil structure, mitigate erosion, and bolster ecological stability. This research is essential as it provides a reference for knowledge pertinent to connected issues, which can be utilized to formulate policies that promote sustainability in natural forest ecosystems. This study seeks to ascertain the composition and structure of seedling vegetation in the Girimanik Natural Forest Area, Wonogiri. This research has not been conducted previously. The research methodology employs a quadratic sampling technique. Twenty-five plots, each measuring 5x5 m², were utilized by purposive sampling. This research identified 296 varieties of seedling plants across 30 species and 22 family. The sapling vegetation community in this region is predominantly composed of Pygeum parviflorum (nyampuh; English: Prunus), exhibiting an INP score of 59.24. The computed Shannon-Wiener diversity index in this study was 2.74, indicating a moderate amount of diversity, characterized by a balanced distribution of individual numbers without extreme diversity index values in the Girimanik forest area